1963
DOI: 10.1002/art.1780060106
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis of the cricoarytenoid joint: A clinicopathologic study

Abstract: Arthritis of the cricoarytenoid joint OCcurs much more frequently in patients with rheumatoid disease than has generally been suspected. Seventeen of 64 randomly selected patients with rheumatoid arthritis had one or more symptoms considered to be characteristic of cricoarytenoid arthritis. At postmortem examination, histopathologic changes typical of rheumatoid arthritis were seen in the cricoarytenoid joints in seven of eight patients with rheumatoid arthritis. The abnormal findings on indirect laryngoscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
1

Year Published

1965
1965
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 8 publications
0
27
1
1
Order By: Relevance
“…11 Since then, there have been several studies that have demonstrated a high prevalence of laryngeal abnormalities in patients with RA, with the incidence being higher in females compared with males. [1][2][3][4][5][6][7][8][9][10][11][12] Most reports on laryngeal involvement in RA patients have focused on the CAJ because of the prevailing increase in incidence and the subsequent serious clinical implications. Acute laryngeal involvement can cause swelling of the vocal folds with airway obstruction, and chronic involvement can impair vocal fold mobility with resultant fixation and narrowing of the glottis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Since then, there have been several studies that have demonstrated a high prevalence of laryngeal abnormalities in patients with RA, with the incidence being higher in females compared with males. [1][2][3][4][5][6][7][8][9][10][11][12] Most reports on laryngeal involvement in RA patients have focused on the CAJ because of the prevailing increase in incidence and the subsequent serious clinical implications. Acute laryngeal involvement can cause swelling of the vocal folds with airway obstruction, and chronic involvement can impair vocal fold mobility with resultant fixation and narrowing of the glottis.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Although this involvement is a well-known concept in otolaryngology, obstruction of the airways is a rarely seen complication of rheumatoid arthritis. 6,7 An interesting feature of the case reported here is the repeated postoperative laryngeal obstruction that occurred just after extubation and 3 weeks postoperatively when the physiotherapy program had progressed to ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Involvement of the cricoarytenoid joint has been reported in 26%-86% of patients with rheumatoid arthritis and can be asymptomatic. 8,9 Furthermore, the severe discomfort characteristic of rheumatoid disease can lead the clinician to overlook cricoarytenoid involvement. 5,10,11 Although first reported in 1880, greater attention has been paid to cricoarytenoid arthritis following Montgomery's 1955 publication on rheumatoid arthritis of the larynx.…”
Section: Objectif : Présenter Un Cas D'obstruction Des Voies Respiratmentioning
confidence: 99%
“…The joint controls abduction and adduction of the vocal cords thereby facilitating respiration, as well as protecting the airway and permitting phonation. 9,14 Any synovial articulation can potentially be affected by rheumatoid arthritis. Increased cellularity of the synovium occurs leading to synovial inflammation.…”
Section: Objectif : Présenter Un Cas D'obstruction Des Voies Respiratmentioning
confidence: 99%
See 1 more Smart Citation